Contractions transport exfoliated epithelial cells through the neonatal epididymis. Issue 1 (July 2020) - Weiser, Daniela; Mietens, Andrea; Stadler, Beatrix; Ježek, Davor; Schuler, Gerhard; Middendorff, Ralf
Abstract : Contractions of the adult epididymal duct are well known in the context of sperm transport. Some reports also describe contractions of the epididymal duct during development, but data about their character, regulation and function are sparse. In the foetal human epididymis we found luminal cells and could identify them as exfoliated epithelial cells originating from the epididymis and not from testis by using antibodies against neutral endopeptidase as an epithelial epididymal duct marker. Exfoliated cells were also found in the epididymal duct after birth. Time-lapse imaging revealed directional transport of luminal cells in the neonatal rat epididymis interrupted by pendular movement. Spontaneous contractions were discovered in the neonatal epididymis and an association between these contractions and the transport of the luminal cells could be observed. Both, transport and spontaneous contractions, were affected significantly by substances known to contract (noradrenaline) or relax (the phosphodiesterase 5 inhibitor sildenafil) smooth muscle cells. Immunohistochemistry showed staining for the proliferation marker proliferating-cell-nuclear-antigen (PCNA) in cells of the ductal lumen of the neonatal rat epididymis indicating the extrusion of cells also during proliferation. Our data showed spontaneous contractions of the immature epididymal duct associated with the transport of exfoliated luminal cells before the first occurrence of sperm cells. Results suggest an important role including both (i) a mechanical place holder function of exfoliated luminal cells (ii) together with a novel idea of organized waste disposal of these cells during development.